Evaluación del proceso de crédito y su impacto en la Liquidez de la empresa “Juan Pablo Mori E.I.R.L.”; durante El año 2013 - Pérez Pinedo, Hugo Nicanor (2015)
Evaluate the process based on the character, capacity, capital, credit conditions and was important because it allowed us to establish their impact on the liquidity of the company “JUAN PABLO MORI E.I.R.L.” during 2013. The research was conducted on the basis of a single population, since it described each of the study variables ; the process variables of credit and the impact on liquidity was assessed ; was measured once, the same as described and analyzed, then the processes evaluated and finally recommendations. The company did not check credit procedures correctly ie personnel to achieve the sale has provided loans without analyzing their ability to pay debts it has with another entity, this makes it incurred a high cost for non-recoverability of accounts receivable and the loss of a high volume of use. In general conclusion was diagnosed with the current status of policies and procedures of the lending company “JUAN PABLO MORI E.I.R.L.” where the results of the delinquent portfolio determined the existence of 25 credi ts to public sector companies who achieved a delinquency S / 128,356.87 representing 10 % of the total portfolio .